Possible Association of High Urinary Magnesium and Taurine to Creatinine Ratios with Metabolic Syndrome Risk Reduction in Australian Aboriginals - Atsumi Hamada; Takashi Taguchi; Hideki Mori; Marjorie Thorpe; Yukio Yamori; Mari Mori (Cardiology Research and Practice)
Background. Because of the epidemic of metabolic syndrome (MS) in Australian Aboriginals known for their higher cardiovascular mortality and shorter life expectancy, we analyzed the possible relationship of their MS risks with the current dietary custom. Methods. The subjects were 84 people aged 16–79 years. The health examination was conducted according to the basic protocol of WHO-CARDIAC (Cardiovascular Diseases and Alimentary Comparison) Study. Results. The highest prevalence among MS risks was abdominal obesity (over 60%). After controlling for age and sex, the odds of obesity decreased significantly with high level of urinary magnesium/creatinine ratio (Mg/cre) (OR, 0.11; 95% CI, 0.02–0.57; P<.05). The significant inverse associations of fat intake with Mg/cre and of fast food intake with urinary taurine/creatinine ratio were revealed. Conclusions. The high prevalence of obesity in the Aboriginal people of this area may partly be due to the reduction of beneficial nutrients intake including Mg and taurine.